Socio-Economic Impact of Gold Mining on the Community of Wamsaid Hamlet, Dava Village, Waelata District, Buru Regency. - Besan, Yuniati; Pinoa, Wiclif Sepnath; Salakory, Melianus (Jurnal Pendidikan Geografi Unpatti, 2024)
This study aims to investigate the social and economic impacts of gold mining in Gunung Botak, especially in Wamsaid Hamlet, Dava Village, Waelata District, Buru Regency. From the social impact aspect, this study focuses on analyzing social interactions and conflicts arising from gold mining activities. The study results indicate that social interactions among gold miners involve collaboration and assistance in mining equipment, gold material excavation, and the gold panning process. On the other hand, there is a social conflict related to fights over ownership of mining land, where misunderstandings regarding the boundaries of each party's land ownership contribute to the conflict. Regarding economic impact, gold mining in Wamsaid Hamlet has a significant positive effect. The income from gold mining activities has proven significant and can meet household economic needs, including clothing, food, and housing. In addition, this income also plays a role in supporting children's educational needs, including facilitating education at a higher level.